A systematic review and meta-analysis: clinical outcomes of recurrent pregnancy failure resulting from preimplantation genetic testing for aneuploidy - Liang, Zhuo; Wen, Qiuyue; Li, Jingjing; Zeng, Dingyuan; Huang, Pinxiu (Frontiers in Endocrinology, 2023)
Background: Preimplantation genetic testing for aneuploidy (PGT-A) is an emerging technology that aims to identify euploid embryos for transfer, reducing the risk of embryonic chromosomal abnormalities. However, the clinical benefits of PGT-A in recurrent pregnancy failure (RPF) patients, particularly in young RPF patients, remains uncertain. Objective and rationale: This meta-analysis aimed to determine whether RPF patients undergoing PGT-A had better clinical outcomes compared to those not undergoing PGT-A, thus assessing the value of PGT-A in clinical practice. Search methods: We systematically searched PubMed, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data, and VIP Database for Chinese Technical Periodicals (VIP) from 2002 to 2022. Thirteen published studies involving 930 RPF patients screened using PGT-A and over 1,434 RPF patients screened without PGT-A were included in this meta-analysis. Clinical outcomes were evaluated based on embryo transfers after PGT-A (n=1,015) and without PGT-A (n=1,799). Clinical outcomes: The PGT-A group demonstrated superior clinical outcomes compared to the in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) group. The PGT-A group had a significantly higher implantation rate (IR) (RR=2.01, 95% CI: [1.73; 2.34]), clinical pregnancy rate (CPR) (RR=1.53, 95% CI: [1.36; 1.71]), ongoing pregnancy rate (OPR) (RR=1.76, 95% CI: [1.35; 2.29]), live birth rate (LBR) (RR=1.75, 95% CI: [1.51; 2.03]), and significantly lower clinical This is a provisional file, not the final typeset article miscarriage rate (CMR) (RR=0 .74, 95% CI: [0.54; 0.99]). Subgroup analysis based on patient age (under 35 years and 35 years or older) showed that both PGT-A subgroups had significantly better CPR (P<0.01) and LBR (P<0.05) values compared to the IVF/ICSI groups. Summary: This metaanalysis demonstrates that PGT-A in RPF patients, is associated with improved clinical outcomes, including higher IR, CPR, OPR, and LBR values, and lower CMR compared to the IVF/ICSI group. These findings support the positive clinical application of PGT-A in RPF patients.